STUDENTS’ ANXIETY IN READING COMPREHENSION AT SMK NEGERI 15 SAMARINDA - Ade Ismail Ramadhan Hamid; Muhammad Geralma Putra; Khusnul Khatimah (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2025)
This study investigates the level and causes of students’ anxiety in reading comprehension at SMK Negeri 15 Samarinda. The urgency of this research lies in the increasing challenge students face in understanding English texts, which often hinders their language learning progress. Using a qualitative descriptive design, data were collected through questionnaires and interviews to explore students’ emotional responses and the factors contributing to reading anxiety. The findings revealed that approximately 67.7% of students experienced anxiety when reading English texts. The main sources of anxiety were unknown vocabulary (71%), unfamiliar cultural contexts (69%), and foreign topics (68%), while personal factors included fear of making mistakes (72%) and concern about reading outcomes (57%). The novelty of this study lies in its in-depth identification of linguistic and personal factors influencing reading anxiety, contributing to the development of more effective reading strategies in English language education.